(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
Public-private partnerships (PPPs) have emerged as a critical mechanism for promoting sustainable development, particularly in the context of higher education institutions. This field study explores the role and impact of PPPs at Future University, focusing on how PPPs contribute to achieving the university’s sustainable development goals. The study uses a descriptive approach by distributing (80) questionnaires to Future University staff, which were analyzed using SmartPLS V.4. The results reveal that PPPs at Future University facilitated infrastructure development, enhanced academic programs, and promoted research initiatives aligned with sustainability goals. However, challenges such as aligning stakeholder interests, ensuring long-term commitment, and maintaining transparency were identified as barriers to maximizing the potential of these partnerships. The study concludes that while PPPs offer significant opportunities to promote sustainable development in higher education, their success depends on strong governance frameworks, clear communication, and shared value creation among all stakeholders. The study provides recommendations to strengthen existing partnerships and guide future collaborations at Future University and similar institutions.